EVALUATION OF TWO-FACTOR AUTHENTICATION METHOD IN IMPROVING AUTHENTICATION SECURITY ON SSL VPN (Case Study of PT. Kanmo Group) - Muhamad Akbar Prasetyo; Nur Chalik Azhar (Jurnal Riset Informatika, 2025)
The increasing use of remote access in corporate environments through Virtual Private Networks (VPNs) requires additional security measures to protect corporate data and systems from cyber threats. In Indonesia, several data leakage cases involving large companies have revealed vulnerabilities in existing security systems, highlighting the importance of stronger data protection. At PT Kanmo Group, the VPN used is still vulnerable to security threats such as brute force attacks and credential theft, because it has not implemented 2FA in increasing its security. To overcome this problem, this research aims to improve SSL VPN security by implementing 2FA as an additional layer in the user authentication process. The research methodology includes problem identification, literature study, implementation, and simulation of system testing using an experimental approach. The results showed that the implementation of 2FA significantly improved VPN access security, reduced the risk of credential leakage, and provided a basis for recommendations for companies in strengthening their security systems. This research is expected to be a reference for the development of a more reliable remote access security system in the corporate environment.